2021
DOI: 10.37256/nat.3120221040
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Electrosynthesized Cobalt Doped Zinc Selenide Thin Films Deposited at Varying Time

Abstract: Time optimized cobalt-doped zinc selenide thin films have been successfully electrodeposited on fluorine-doped tin oxide substrates. The films were deposited at the varying time of 1 min, 3 mins, and 5 mins respectively. Film thickness, optical, structural, electrical, and morphological properties of the deposited thin films were evaluated. Film thickness estimated using the gravimetric method increased from 294.35 nm to 399.62 nm as deposition time increased. Optical properties showed that the absorbance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Similar effects on bandgap due to changes in deposition time using electrodeposition techniques have been reported by Refs. 40 and 41, demonstrating therefore a positive correlation between deposition time and thickness of the film 42 …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar effects on bandgap due to changes in deposition time using electrodeposition techniques have been reported by Refs. 40 and 41, demonstrating therefore a positive correlation between deposition time and thickness of the film 42 …”
Section: Resultsmentioning
confidence: 86%
“…40 and 41, demonstrating therefore a positive correlation between deposition time and thickness of the film. 42…”
Section: Ellipsometry Characterizationmentioning
confidence: 99%
“…The optical studies indicate the doped samples to have a red shifted absorption spectrum and a decreased bandgap about 3.3eV. It has also been investigated how doping of Mg transition metal affected the characteristics of ZnSe film and reported that the energy bandgap of film was 3.48eV, the particles was 11 nm in dimension, and the Mg was entirely bonded in the ZnSe lattice 34) , 35) . Due to the fact that most II-VI based dilute magnetic semiconductors typically exhibit anti ferromagnetic or spin glass ordering, the II-VI semiconductor doped with a magnetic element has also been researched but has only found a limited number of uses.…”
Section: Introductionmentioning
confidence: 99%